Food materials science and engineering - Bhandari, Bhesh; Roos, Yrjö H. (Chichester, West Sussex, UK ; Ames, Iowa : Wiley-Blackwell, 2012)
"Food Materials Science and Engineering covers a comprehensive range of topics in relation to food materials, their properties and characterisation techniques, thus offering a new approach to understanding food production and quality control"--
Includes bibliographical references and index.
Print version record.
Keywords: Food -- Composition; Food -- Analysis; TECHNOLOGY & ENGINEERING -- Food Science; TECHNOLOGY & ENGINEERING -- Agriculture -- Animal Husbandry; Food -- Analysis; Food -- Composition; Electronic books